Restoration of Degraded Urban Wetlands (by the Case of Sovski Ponds in Kyiv) - Шищенко, П.; Гавриленко, Олена Петрівна; Циганок, Євген Юрійович; Муніч, Н. (Київський національний університет імені Тараса Шевченка, 2022)
The article is devoted to the problem of the preservation of urban wetlands as the most vulnerable valuable ecosystems in the conditions of rapid urbanization, which need to be protected. It researches the current state of the Sovky tract (and the lower cascade wetlands of the Sovski Ponds located within it) in the center of Kyiv. Despite the strong urban influence, the rich floristic and faunal diversity of the studied area has been revealed. The value of urban wetlands for Kyiv is determined by the vital ecosystem services provided to the local community. Such services include, first of all, regulation of the microclimate, moisture and nutrients distribution in the soil, habitats preservation for the rare species of animals and plants, regulation of the groundwater levels, pollution filtration, waste adsorption, oxygen production and carbon dioxide absorption, water quality improvement, mitigation of the climate change consequences, creation of the favourable conditions for recreation, etc. As a result of field surveys of the Sovky tract, the complete decline of the territory and the degradation of valuable wetlands have been indicated. We have investigated the main geoecological conflicts caused by littering of the territory with household and construction waste, persistent pollution of the water bodies caused by untreated sewage due to unauthorized intrusions of residents into the household sewers, chemical and noise pollution from the road infrastructure, grass burning in spring, etc. The spatial localisation of all conflicts within the Sovky tract is shown on the relevant map. The negative consequences of the long-term unresolved conflicts for the functioning of the wetlands and the quality of the ecosystem services they provide have been identified. Given the perspective of development in the study area of the ecopark and a fairly general idea of the essence of this concept, we proposed to include wetlands of Sovky tract in the Nature Reserve Fund of Kyiv. According to the current legislation, this area meets all the criteria of the category “Regional Landscape Park” (RLP).The main purpose of preserving the unique urban wetlands is the protection of rare species of plants and animals and their natural habitats, which is possible only in the conditions provided for in the RLP reserved zone. In addition, granting the official status of a protected area will make it impossible to build and litter within unique urban wetlands in the future.

Статтю присвячено проблемі збереження міських водно-болотних угідь як найуразливіших цінних екосистем в умовах стрімкої урбанізації, які необхідно зберігати й охороняти. Досліджено сучасний стан урочища Совки у середмісті Києва, у межах якого розташовано водно-болотні угіддя (ВБУ) нижнього каскаду Совських ставків. Попри потужний урбаністичний вплив, виявлено багате видове флористичне й фауністичне різноманіття досліджуваної території. Цінність міських ВБУ для Києва визначається життєво необхідними екосистемними послугами, які надаються місцевій громаді. До таких послуг належать, насамперед, регулювання мікроклімату, розподіл вологи й поживних речовин у ґрунті, збереження оселищ рідкісних видів тварин і рослин, регулювання рівня ґрунтових вод, фільтрація забруднень, адсорбція відходів, продукування кисню й поглинання вуглекислоти, поліпшення якості води, пом’якшення наслідків зміни клімату, створення сприятливих умов для відпочинку населення тощо. У результаті проведення натурних обстежень урочища Совки зазначено повний занепад території’та деградацію цінних ВБУ. Досліджено головні геоекологічні конфлікти, зумовлені засміченням території побутовими й будівельними відходами, стійким забрудненням водойм неочищеними стоками через несанкціоновані врізання жителів у побутову каналізацію, хімічним і шумовим забрудненням з боку дорожньої інфраструктури, весняним випалюванням травостою тощо. Просторову локалізацію всіх конфліктів у межах урочища Совки відображено на відповідній картосхемі. Показано негативні наслідки тривалого нерозв’язання зазначених конфліктів для функціонування ВБУ та якості екосистемних послуг, які вони надають. З огляду на перспективу розбудови на досліджуваній території’ екопарку й загальні уявлення щодо сутності цього поняття, нами запропоновано включити ВБУ урочища Совки до складу природно-заповідного фонду Києва. Згідно з діючим законодавством ця територія відповідає всім критеріям категорії “регіональний ландшафтний парк” (РЛП). Головною метою збереження унікальних міських ВБУ є охорона рідкісних видів рослин і тварин та їхніх природних оселищ, що можливо лише в умовах передбаченої в РЛП заповідної зони. Крім того, надання офіційного статусу природоохоронної території’ унеможливить забудову й засмічення унікальних міських ВБУ в майбутньому.
Відновлення деградованих міських водно-болотних угідь (на прикладі Совських ставків у Києві)
Keywords: міські водно-болотні угіддя; геоекологічні конфлікти; Совські ставки; урбаністичний вплив; природоохоронна територія; urban wetlands; geoecological conflicts; Sovski Ponds; urban impact; protected area